PERAN KOPERASI SYARIAH DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT KOTA PALEMBANG DI ERA NEW NORMAL - Ratna (LA RIBA: Jurnal Perbankan Syariah, 2020)
This study aims to analyze the role of koperasi syariah in improving the welfare of surrounding communities. The analysis is carried out by descriptive analysis method based on the theory obtained through library studies. The results of this study indicate that Islamic Cooperative are now alive and well is Islamic Cooperative who continues to make improvements. The strategy used to adjust conditions, which part should be strengthened and supported so that customers remain loyal to koperasi syariah; and Islamic Cooperative has a role, among others, is to keep the community away from the moneylenders or usury, invites the public to entrust their money to Islamic Cooperative, the micro business community is invited to be more disciplined in managing the financial results of their business, and help people who are just starting a business, or whose business is already running in financing, so that the business can grow and develop, so that prosperity will be achieved.